2011
DOI: 10.1093/ije/dyr181
|View full text |Cite
|
Sign up to set email alerts
|

Author's Response to: Does sexual function survey in Denmark offer any support for male circumcision having an adverse effect?

Abstract: VN. Alternatives for logistic regression in cross-sectional studies: an empirical comparison of models that directly estimate the prevalence ratio. BMC

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 9 publications
0
9
0
Order By: Relevance
“…23,60 Just as with various forms of non-therapeutic FGA, male circumcision has been associated with numerous sexual difficulties, ranging from reduced sensitivity in the exposed glans, to problems with orgasm, to pain in the receptive female partner. [64][65][66] Nevertheless, many, if not most, circumcised men report being able to enjoy their sexual experiences, notwithstanding the loss of erotogenic tissue 67,68 (see Box 1 for further discussion). Just as with FGA, male genital cutting can take many different forms.…”
Section: The Harms Of Mgamentioning
confidence: 99%
See 1 more Smart Citation
“…23,60 Just as with various forms of non-therapeutic FGA, male circumcision has been associated with numerous sexual difficulties, ranging from reduced sensitivity in the exposed glans, to problems with orgasm, to pain in the receptive female partner. [64][65][66] Nevertheless, many, if not most, circumcised men report being able to enjoy their sexual experiences, notwithstanding the loss of erotogenic tissue 67,68 (see Box 1 for further discussion). Just as with FGA, male genital cutting can take many different forms.…”
Section: The Harms Of Mgamentioning
confidence: 99%
“…71 For example, in an oft-cited study purporting to show no adverse effect of circumcision on sexuality, "several questions were too vague to capture possible differences between circumcised and not-yet circumcised participants [such that] non-differential misclassification of sexual [outcomes] probably favored the null hypothesis of no difference, whether an association was truly present or not." 66 Finally, due to the fact the foreskin "can be stretched, rolled back and forth over the glans, and otherwise manipulated during sex and foreplay, [allowing] for a range of sexual functions -along with their concomitant sensations -that are physiologically impossible if this tissue is removed … To say that circumcision has 'little or no effect' on sexual experience [is] to adopt an extremely narrow conception of that term". …”
Section: Medicolegal and Bioethics Downloaded From Httpsmentioning
confidence: 99%
“…), it must be remembered that a lack of statistical significance does not entail a lack of underlying effect ( 31 ). For example, in one of the studies cited by the CDC, “several questions were too vague to capture possible differences between circumcised and not-yet circumcised participants [such that] non-differential misclassification of sexual [outcomes] probably favored the null hypothesis of no difference, whether an association was truly present or not” [( 32 ), p. 313].…”
Section: Harmmentioning
confidence: 99%
“…(p. 313) [14] Morris and Krieger also misclassify a poor-quality study by Masters and Johnson from the 1960s as a highquality study, even though its methods were not adequately reported and its findings had been previously discredited [15], further skewing their "systematic review". 2 In an empirical study (N = 163) of penile fine-touch pressure thresholds in circumcised versus genitally intact men, Sorrells et al previously had reported that, "The finetouch sensitivity of 19 locations on the penis was measured using Semmes-Weinstein monofilament touch-test… When compared with the most sensitive area of the circumcised penis, several locations on the uncircumcised penis … that are missing from the circumcised penis were significantly more sensitive."…”
Section: Consistent With the Latter Interpretation Frisch Has Statedmentioning
confidence: 99%